Host factors and risk of pin site infection in external fixation: A systematic review examining age, body mass index, smoking, and comorbidities including diabetes - Marie Fridberg; Mats Bue; Jan Duedal Rölfing; Søren Kold (Journal of Limb Lengthening & Reconstruction, 2022)
Introduction: Host factors affecting pin site infections were selected by The Pin site Consensus Group, using a modified Delphi approach, to be one of the top 10 priorities to investigate how to reduce rates of pin site infections, improve clinical management, and inform research. The aim of this study was to perform a systematic literature review of the association between host factors and pin site infection, focused on age, smoking, body mass index, and comorbidities, in particular diabetes. Materials and Methods: The literature search strategy was developed as advised in the Cochrane Handbook for Systematic Reviews of Interventions following the PRISMA guidelines with the help from a scientific librarian. The protocol was registered in the International Register of Systematic Reviews, PROSPERO (ID: CRD42021273305). The literature search was executed in three electronic bibliographic databases, including Embase MEDLINE (1111 hits) and CINAHL (2066 hits) through Ovid and Cochrane Library CENTRAL (387 hits). Results: A total of 3564 titles were found. 3162 records were excluded by title and abstract screening. 140 studies were assessed for full-text eligibility. All excluded studies were not reporting specific numbers of patients with pin site infection and the associations of interest. 11 studies were included for data extraction. The included studies were all designed retrospective, and the risk of bias assessment was done using Joanna Briggs Institute risk appraisal tool. The extracted data are presented as results in tabular summaries. This review reveals an increased risk of pin site infection associated with increased HbA1C level in diabetic patients and congestive heart failure in diabetic patients. An increased risk of pin site infection was associated with a lower ASA score. None of the included studies found any association between pin site infection and smoking, age, or body mass index. Conclusion: This systematic literature search identified a surprisingly low number of studies examining the association between pin site infection and the specific host factors. Thus, this review most of all serves to demonstrate a gap of evidence about the correlation between host factors and risk of pin site infection, and further studies are warranted.